Breast Cancer: Current Insights into Epidemiology, Molecular Mechanisms, and Therapeutic Approaches - Mangunsong, Sonlimar; Rachmadhini, Aninditha Rachmah; Simamora, Sarmalina (Jurusan Farmasi, Poltekkes Kemenkes Palembang, 2024)
Breast cancer is the most commonly diagnosed cancer and a leading cause of cancer-related mortality among women worldwide. Despite significant advancements in molecular understanding and the development of targeted therapies, the management of this disease remains challenging, particularly in low-resource settings. This article reviews the global and regional epidemiology of breast cancer, highlighting its increasing incidence and the disparities in outcomes between high- and low-income countries. It also examines the molecular mechanisms underlying tumor growth, focusing on genetic mutations, hormone receptor status, and HER2 expression. Furthermore, the article explores innovative therapeutic strategies, including targeted therapies, immunotherapy, and combination treatments, which offer promising results for improving patient outcomes. The role of predictive tools, such as Oncotype DX and Mammaprint, in personalizing treatment strategies is also discussed. By examining tumor heterogeneity, biomarker-based approaches, and advances in early detection, this research aims to provide a comprehensive perspective on the evolving landscape of breast cancer management and the potential for more effective and individualized therapies.